Pengaruh ROA, NIM, dan BOPO terhadap Harga Saham Perbankan LQ20 di Bursa Efek Indonesia Periode 2016-2022 Menggunakan Analisis Data Panel - Djoko Wijono; Bambang Sugeng Dwiyanto; Andriya Risdwiyanto; Jemadi Jemadi (Jurnal Maksipreneur, 2023)
This study aims to determine the effect of Return on Assets (ROA), Net Interest Margin (NIM), and Operating Expenses on Operating Income (OEOI) on the Share Price of banks in the LQ20 listed on the Indonesia Stock Exchange (IDX) during 2016 to 2022. The sample used in this study consisted of 4 banks in the LQ20 listed on the IDX. This study uses panel data obtained from Bank Indonesia reports and audited financial reports on banking companies listed on the IDX. By using the Common Effect Model with Eviews, the F-test result shows that the ROA, NIM, and BOPO variables simultaneously have a significant effect on the Stock Price. Based on the t-test results, the ROA has a positive effect on the Stock Price with a statistically strong level of significance. The NIM has a negative effect on Stock Price, while the BOPO has no effect on the Stock Price. The prediction of the three independent variables on Stock Price is 92.9%, while 37.1% remaining is influenced by other factors that are not included in the research model.